SISTEM INFORMASI PENGIRIMAN BARANG PADA CV. DANAU KERINCI EKSPRES: Data Processing, Information System Delivery - Louis, Ahmad; Agustini, Yolanda (JURNAL AKADEMIKA, 2017)
One of the elements involved in data processing is a program or application. Processing a data can not be separated from factors that affect both data managers and data processed itself. Based on the author's observations when doing research in Cv. Danau Kerinci Express, for data processing delivery of goods has not been computerized therefore the author aims to Design a system of information delivery of goods on the Cv. Danau Kerinci Express and modify into a new system so that the new system can overcome the weaknesses that exist in the old system. And to present the Information Delivery of Goods and know the user's response to the implementation of information delivery system application program on Cv.DanauKerinci Express. In doing research the author uses several methods such as, interview methods, observation, field research, literature and laboratory studies. With the Information System Delivery of goods by using Netbeans, is expected to help shipping companies to facilitate the process of delivery of goods in order not to happen things that can harm the company.